Sustainable Peacebuilding and Social Justice in Times of Transition Findings on the Role of Education in Myanmar - Lopes Cardozo, Mieke T.A; Maber, Elizabeth J.T (Springer International Publishing : Imprint: Springer, 2019)
This book offers a unique insight into the ways in which education systems, governance, and actors at multiple scales interact in initial steps towards building peace. It presents a spectrum of recently conducted research in the context of Myanmar, a society in the midst of challenging transitions, politically, socio-culturally and economically. Divided in 3 thematical research areas, the first part on Myanmar's policy landscape aims to unravel the integration of peacebuilding into the education sector at macro and micro policy levels. The second part examines the role teachers play in processes of peacebuilding, and the third part examines ways in which formal and non-formal peacebuilding education programs address the agency of youth in Myanmar. This book is an essential guide for students embarking in the field of education, conflict and peacebuilding.